High-temperature behavior of housed piezoelectric resonators based on CTGS - M. Schulz (Copernicus Publications, 2021)
A temperature sensor based on piezoelectric single crystals allowing stable operation in harsh environments such as extreme temperatures and highly reducing or oxidizing atmospheres is presented. The temperature dependence of the mechanical stiffness of thickness shear mode resonators is used to determine temperature changes. The sensor is based on catangasite (Ca3TaGa3Si2O14 – CTGS), a member of a langasite crystal family. CTGS exhibits an ordered crystal structure and low acoustic losses, even at 1000 ∘C.